Social Media Use and Its Effects on Self-Esteem among Young Adult in Brazil - Barbosa, Amanda (International Journal of Psychology, 2024)
Purpose: The aim of the study was to analyze the social media use and its effects on self-esteem among young adult in Brazil. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A study in Brazil found that frequent social media use was linked to lower self-esteem among young adults. Comparing themselves with others online, especially in appearance and lifestyle, negatively affected participants' self-perceptions. Social media use was associated with feelings of inadequacy and social isolation, although positive interactions could mitigate self-esteem issues. Overall, the study highlighted the intricate relationship between social media and self-esteem in Brazilian youth. Unique Contribution to Theory, Practice and Policy: Social comparison theory, self-presentation theory & uses and gratifications theory may be used to anchor future studies on the social media use and its effects on self-esteem among young adult in Brazil. Educational programs and interventions should be developed to promote healthy social media use and enhance self-esteem among young adults in Brazil. Government agencies could collaborate with social media companies to develop and enforce policies that address harmful content, cyberbullying, and unrealistic beauty standards on online platforms.